PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS X PADA MATA PELAJARAN PPKN DI SMA NEGERI 1 GOWA - Kasmawati, Andi; Bakhtiar, Bakhtiar; Bangngalino, Desi bangalino (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
This research aims to: (1) To find out the teacher's learning planning using the Problem based learning model to increase students' interest in learning in class X SMAN 1 Gowa. (2) Examining the implementation of the Problem based learning model in Civics subjects at SMAN 1 Gowa. (3) Evaluate the effectiveness of the Problem based learning model in increasing the learning interest of class X students at SMAN 1 Gowa. This research uses a qualitative approach with a descriptive research type. The type of data used is qualitative data with primary and secondary data sources. Data collection techniques through observation, interviews and documentation. Data obtained from interviews with PPKn teachers and class X students. Checking the validity of the data using source triangulation techniques with data analysis techniques consisting of data reduction, data presentation and drawing conclusions. The results of the research show that: (1) Planning the Problem based learning Model in increasing students' interest in learning is carried out by the teacher by paying attention to the steps in the PBL model which are linked to the teacher's teaching module or RPP (2) Implementing the Problem based learning Model in increasing interest in learning based on the indicators in the PBL model and KD learning that has been determined to involve selecting interesting cases, forming effective groups, and active group discussions (3) From the evaluation carried out it can be seen that the problem based learning model can increase students' interest in learning proven by paying attention to students' active participation in group discussions, increased curiosity and motivation to learn, as well as satisfactory learning results.Keywords: Problem based learning Model, Student Interest in Learning